The Nūr-Ẓulmah Framework in Islamic Psychology: A Conceptual Reconstruction of Ibn 'Aṭā'illāh as-Sakandarī's Thought - Achmad Beadie Busyroel Basyar; Achmad Khudori Soleh; Siti Mahmudah; Ahmad Naweed Rahimi Khamoush (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This article examines the concepts of nūr (light) and ẓulmah (darkness) in the thought of Ibn 'Aṭā'illāh as-Sakandarī and their implications for Islamic psychology. While historical studies of the Islamic soul (nafs) frequently emphasize ontological descriptions and normative ethics, they rarely articulate the functional dynamics through which spiritual components produce moral behavior. Addressing this gap, this study conceptually reconstructs the operational roles of nūr and ẓulmah in relation to the 'aql (intellect), baṣīrah (spiritual insight), and qalb (heart). Employing qualitative content analysis, the study systematically unitizes, categorizes, and synthesizes primary textual data from al-Ḥikam and its authoritative classical commentaries. The findings indicate that the human psyche is structured by internal faculties interacting with transcendental epistemic inputs (nūr) and egoistic distortions (ẓulmah). Nūr manifests in graduated forms (intibāh, iqbāl, wiṣāl) that progressively enhance moral cognition and activate the baṣīrah. Conversely, ẓulmah operates through base desires that obscure ethical orientation. Rather than positioning this framework in binary opposition to contemporary psychology, the study places as-Sakandarī in constructive dialogue with psychoanalysis and positive psychology, highlighting how Islamic psychology introduces a theocentric dimension to internal conflict and human flourishing. Ultimately, this study offers a conceptual reconstruction that bridges classical Shadhiliyyah thought with modern discourse on moral development, providing a theoretical foundation relevant to contemporary Islamic educational and therapeutic settings